Workplace learning : a study of learning approaches in two organisations in Sarawak - Bong, Er Huen. (unimas, 2007)
The purpose of this study is to analyze the types of learning approaches used in two organisations in Sarawak and the factors influencing it. A survey questionnaire was used to collect data for this study. Eighty respondents were selected from two organisations: Public Work Department (PWD) Sarawak and Syarikat SESCO Berhad. The data gathered were analyzed using both descriptive and inferential statistics. Descriptive statistics was used to describe respondents' personal characteristics such as gender, age, educational level, length of service and monthly income. Inferential statistics such as Pearson Correlation Coefficient was used to determine whether there exists a significant relationship between the independent variables and learning approaches. The findings show that the majority of respondents (78.7%) frequently use informal learning approaches such as conducting discussions with colleagues and supervisors, and obtaining information through resource centers, the Internet, books, magazines and other reading materials in the workplace. In contrast, only a minority of the respondents (11.2%) very often use formal learning approaches in the workplace. Analysis of the results also found that there exist significant positive relationships between the two independent variables — learning attitude and environmental support — and learning approaches used in the workplace. However, both relationships are weak: between learning attitude and learning approaches (r = 0.540), and between environmental support and learning approaches (r 0.443). Several recommendations are suggested to the organizations, human resource practitioners and for future research in order to encourage continuous learning in the workplace and to help enhance employees' work performance.